2022
DOI: 10.1111/ijfs.15658
|View full text |Cite
|
Sign up to set email alerts
|

A novel polysaccharide prepared from Chrysanthemum morifolium cv. Fubaiju tea and its emulsifying properties

Abstract: In this study, a novel chrysanthemum polysaccharide (CP) was obtained and investigated from Chrysanthemum morifolium tea in Hubei province, China. Molecular characterisation and emulsifying properties of the CP were elucidated. The effects of different factors, including storage time, metal ions, pH value and heat treatment, were studied on the stability of emulsion. Results showed that the mean particle diameter (MPD) (d 32 ) varied from 5.54 to 0.49 lm with the polysaccharide concentration ranging from 0.5wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Recent studies showed that a novel polysaccharide obtained from C. morifolium cv. Fubaiju had good emulsifying property and stability (Zhang et al, 2022 ). However, there is little research on the development of Chrysanthemum food products.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that a novel polysaccharide obtained from C. morifolium cv. Fubaiju had good emulsifying property and stability (Zhang et al, 2022 ). However, there is little research on the development of Chrysanthemum food products.…”
Section: Introductionmentioning
confidence: 99%